Social Media Marketing Strategies of Women Entrepreneurs in Makassar's Home-Based Food Business - Riu, Isma Azis (International Humanity Advance, Business & Sciences, 2025)
This qualitative study explores how women entrepreneurs in Makassar utilize social media platforms to market their home-based food businesses. Using a multiple case study approach, this research examines the digital marketing strategies, content creation processes, and customer engagement techniques employed by women food entrepreneurs. The study investigates how these entrepreneurs leverage Instagram, Facebook, and WhatsApp to build brand identity, reach customers, and generate sales without significant capital investment. Data will be collected through in-depth interviews with successful women food entrepreneurs and analysis of their social media content. The findings aim to reveal indigenous digital marketing practices adapted to local cultural contexts and resource constraints, contributing to understanding digital entrepreneurship among women in emerging markets.